Syphilis-Associated Proteinuria and Hepatitis in the Setting of Human Immunodeficiency Virus (HIV) Co-Infection. (22nd September 2022) - Jain, Hanish; Singh, Garima; Asiago-Reddy, Elizabeth
Abstract : Syphilis has long been known as "the great imitator", mimicking a wide variety of diseases, and often its diagnosis is delayed or missed. It remains an important public health issue that continues to occur at high rates among patients with HIV. We report a case of a 52-year-old man who presented with a constellation of unusual symptoms highlighting that syphilis should be included in the differential diagnosis in patients with HIV presenting with abnormal liver enzymes, rash, proteinuria, conjunctivitis, and/or sexual risk factors.